The Role of Good Corporate Governance in Influenced Accounting Conservatism of Manufacturing Companies in Indonesia - Aini, Nurul; Pirmaningsih, Lilik; Pradika, Novaldy Arief (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: This study aims to examine the role of good corporate governance in accounting conservatism. Methodology: This study uses a sample of manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2021 period, with a total sample of 72 company-years. The test uses SPSS 25. Findings: The study found that independent commissioners and profitability have a significant positive effect on accounting conservatism, while managerial ownership and company size do not affect accounting conservatism. Implications: This study provides implications for the theory of accounting conservatism, where the factors of independent commissioners and profitability have a significant effect on accounting conservatism. The presence of independent commissioners in the company will ensure that the company's financial reporting process is well-monitored so that the company is more careful in carrying out its financial reporting. Similarly, with profitability, the presence of high profitability will increase the amount of retained earnings, and the company tends to use more conservative accounting principles to regulate earnings to appear more flat and less volatile.